LncRNA TUSC7 Inhibits Cell Proliferation in Chronic Lymphocytic Leukemia by Modulating the miR‐211‐5p/SLC37A3 Axis - Xu‐Li Wang; Jia Mei (Kaohsiung Journal of Medical Sciences)
ABSTRACT Chronic lymphocytic leukemia (CLL) is a malignant lymphoproliferative disorder. Long non‐coding RNAs (lncRNAs) have been implicated in various regulatory processes and cancer development. Among these, lncRNA tumor suppressor candidate 7 (TUSC7) has been identified as a tumor suppressor gene. We herein measured TUSC7 expression using RT‐qPCR and investigated its biological role in CLL through gain‐of‐function experiments. Our results revealed that TUSC7 expression was significantly lower in CLL patients compared to healthy controls, and its downregulation was associated with poor prognosis. Meanwhile, TUSC7 overexpression inhibited cell proliferation while promoting cell apoptosis. Mechanistically, TUSC7 interacted with miR‐211‐5p, thereby regulating the downstream target gene, solute carrier family 37 member 3 (SLC37A3). Further rescue experiments demonstrated that silencing SLC37A3 or upregulating miR‐211‐5p reversed the effects of TUSC7 elevation on cell proliferation and apoptosis. In conclusion, our findings suggest that TUSC7 regulates cell proliferation in CLL through the miR‐211‐5p/SLC37A3 axis.